Nanodiamonds as traps for fibroblast growth factors: Parameters influencing the interaction. (15th August 2022) - Mikesova, Jana; Miliaieva, Daria; Stenclova, Pavla; Kindermann, Marek; Vuckova, Tereza; Madlikova, Marcela; Fabry, Milan; Veverka, Vaclav; Schimer, Jiri; Krejci, Pavel; Stehlik, Stepan; Cigler, Petr
Abstract: Fibroblast growth factors (FGFs) deliver external cell communication signals, to regulate mammalian development, metabolism and homeostasis. Blocking the FGF interactions with their receptors at the cell membrane is one of the promising strategies for treatment of diseases related to dysregulated FGF signaling, such as cancer, metabolic syndromes, and developmental disorders. Recently, detonation nanodiamonds (NDs) with positive ζ-potential were identified as highly effective and selective FGF binders, sequestering FGF molecules and preventing their interaction with receptors under physiological conditions, thus potentially eliminating the effect of FGF overexpression. Here, we investigated the influence of ND origin (detonation vs. high-pressure high-temperature), surface modification, size and separation/purification steps on the sequestration ability and binding affinity of FGF2, a representative member of the FGF family. We measured FTIR and Raman spectra of the NDs, assessed their colloidal behavior and ζ-potential, and correlated their properties with FGF2 interaction levels. Using Western blot and ELISA, we quantified the strength of the interaction between detonation NDs and FGF2. All NDs with positive ζ-potential sequestered FGF2 at its physiologically relevant concentrations. Hydrogenated detonation NDs showed the highest binding capacity. Using Langmuir model, we estimated the apparent dissociation constant between FGF2 and detonation ND with positive ζ-potential to be in the nanomolar range in full fetal bovine serum. Because such tight interaction between a protein and a solid nanoparticle occurred in ∼10 5 -fold molar excess of serum proteins, we believe that NDs can potentially be used in vivo as selective FGF traps to regulate disorders caused by aberrant FGF signaling. Graphical abstract: Image 1